PENGARUH METODE PEMBELAJARAN ALM (AUDIO LINGUAL METHOD) TERHADAP KETERAMPILAN PENGUCAPAN (PRONUNCIATION) PADA SISWA KELAS 4 SDN PAKULONAN BARAT II KABUPATEN TANGERANG - Mutia Saidah; Ina Magdalena; Azhar, Arry Patriasurya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background to this research is the large number of students with low basic English pronunciation skills due to several internal and external factors, such as less effective learning methods. This research uses an audio lingual method which can be used as an alternative for the learning process to make it more effective so that it can improve students' basic English pronunciation skills. This research aims to determine the differences in learning outcomes given the audio lingual method and students who are not given the audio lingual method. The results of this research indicate that the use of the audio lingual method is the right step to help students process basic pronunciation skills better and more correctly, however the use of the audio lingual method has weaknesses such as teachers will complain about the amount of time it takes (long), and students will complain about the boredom caused by the constant use of drill patterns. This research is research that uses quantitative research methods, using pretest question instruments and posttest questions in the form of English question texts which will be assessed according to assessment indicators. Data collection techniques use tests, observation, interviews and documentation.